The underlying mechanisms behind the Nutri-Grade label's influence on consumers' intake of sugary beverages in Singapore - Chua, Kanric Sing Wei (Nanyang Technological University, 2023)
There has been a growing concern for Singaporeans’ health due to an observed increase in the sugar and salt intake among Singaporeans, which could lead to chronic illnesses such as diabetes and hypertension. Hence, there has been more emphasis on healthier consumption habits. To counter this, the Singapore government has implemented a new mandatory nutritional label known as the Nutri-Grade targeting sugar sweetened beverages (SSBs). In this paper, we will be examining the underlying mechanisms of the Nutri-Grade label in influencing consumers’ consumption of SSBs, namely information asymmetry and salience bias. In order to do so, we conducted an online survey to elicit participants’ willingness-to-pay (WTP) under the respective underlying mechanisms. For the information asymmetry section, we compared their WTP before and after revealing the hidden nutritional information for different beverages from Nutri-Grade A to D, and the multiple price list mechanism was also utilised to elicit participants’ WTP for the salience bias section. Subsequently, regression analysis and statistical tests to test for the significance of our results were performed. Our results have shown that an increase in nutritional information and label size have a positive influence on the participants, increasing their WTP. Therefore, we conclude that information asymmetry and salience bias are potential mechanisms that can be used to encourage consumption of healthier beverages in Singapore. This will be useful in providing some insights for the Singapore government in implementing policies related to the consumption of SSBs in the future.